MTHFR C677T, PT G20120A and FV Leiden as Risk Factors for Thrombosis in Egyptian Pediatric ALL Patients - Ahmed, Mohamed Nagy (AUC Knowledge Fountain, 2015)
Thrombosis is a well-known side effect associated with Acute Lymphoblastic Leukemia (ALL) treatment leading to significant morbidity rates. Thrombosis occurrence in ALL patients seems to be due to the interaction between the disease, the therapy and the possible inherited genetic defects affecting the hemostatic balance. In this study we aimed to assess the prevalence of prothrombotic defects- FV Leiden, MTHFR (Methylene Tetra Hydrofolate Reductase enzyme) C677T & prothrombin (PT) G20210A mutations in Egyptian pediatric ALL patients and its impact on the risk of thrombosis onset as well as to evaluate the impact of the presence of single versus multiple prothrombotic mutations on thrombosis. Sixty three pediatric ALL patients with thrombotic event treated with ALL protocol adopted from SJCRH (Saint Jude Cancer Research Hospital) study XV at the Children's Cancer Hospital in Egypt (CCHE) and 63 matched ALL control patients were enrolled in the study. Restriction fragment polymorphism technique was used to assess the prevalence of the FV Leiden and MTHFR C677T while Allele specific PCR was used for Prothrombin G20210A. Our results showed that MTHFR C677T prevalence between the ALL patients with and without thrombosis was 65% and 38.1% respectively p value = 0.002. The FV Leiden prevalence between the ALL patients with and without thrombosis was 17.5% and 15.9 % respectively p value= 0.81. While the prothrombin G20210A prevalence was 3.2% in both groups. In addition, patients who were older than 10 years or on SR/HR treatment protocol or in induction treatment phase were also at high risk of thrombosis. The presence of MTHFR C677T polymorphism can increase the risk of thrombosis 3 folds more than those patients who didn't have the polymorphism, while FV Leiden and PT G20210A didn't affect the thrombosis risk. Having more than one mutation didn’t show a significant effect on increasing the risk of thrombus incidence (p= 0.087). We concluded that MTHFR C677T is important risk factor for thrombosis in Egyptian pediatric ALL patients. These results may help in the prediction of the thrombosis susceptibility for ALL patients and a prophylaxis therapy may be considered before having the thrombosis. To the best of our knowledge these findings regarding the thrombosis risk factors in Egyptian pediatric ALL patients are first to be reported.